Model Mental dalam Pembelajaran Fisika: Systematic Literature Review - Setiono, Isnaini Agus; Lasiani, Lasiani; Wati, Mustika; Dewantara, Dewi (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
A mental model is one of the important indicators of the success of physics learning. However, proper physics learning is still tricky in facilitating students to construct scientific mental models. This study aims to investigate physics learning activities that can construct students' mental models. A literature-based study was conducted using the Scopus database on 234 articles from 2015-2025, then systematically selected 15 articles that are relevant to the topic. This study reveals that using various visual media in physics learning can build students' mental models. Mechanics, electronics, temperature and heat, and modern physics are the physics learning topics with the most potential for constructing students' mental models. Several articles are not directly related to each other, such as mental models, visual representations, and real-world life, especially at the high school level. This is a potential opportunity to be explored further in further research. The findings of this study contribute significantly to discussing effective physics learning innovations to build students' mental models.